Hair dye and chemical straightener use and breast cancer risk in a large US population of black and white women - Eberle, Carolyn E. (Int J Cancer, 2019)
Many hair products contain endocrine disrupting compounds and carcinogens potentially relevant to breast cancer. Products used predominately by black women may contain more hormonally-active compounds. In a national prospective cohort study, we examined the association between hair dye and chemical relaxer/straightener use and breast cancer risk by race. Sister Study participants (N=46,709), women ages 35–74, were enrolled between 2003–2009, and had a sister with breast cancer but were breast cancer-free themselves. Enrollment questionnaires included past 12-month hair product use. Cox proportional hazards models estimated adjusted hazard ratios (HRs) and 95% confidence intervals (95% CIs) for the association between hair products and breast cancer; effect measure modification by race was evaluated. During follow-up (mean=8.3 years), 2,794 breast cancers were identified. 55% of participants reported using permanent dye at enrollment. Permanent dye use was associated with 45% higher breast cancer risk in black women (HR=1.45, 95% CI: 1.10–1.90), and 7% higher risk in white women (HR=1.07, 95% CI: 0.99–1.16) (heterogeneity p=0.04). Among all participants, personal straightener use was associated with breast cancer risk (HR=1.18, 95% CI 0.99–1.41); with higher risk associated with increased frequency (p for trend=0.02). Non-professional application of semi-permanent dye (HR=1.28, 95% CI 1.05–1.56) and straighteners (HR=1.27, 95% CI 0.99–1.62) to others was associated with breast cancer risk. We observed a higher breast cancer risk associated with any straightener use and personal use of permanent dye, especially among black women. These results suggest that chemicals in hair products may play a role in breast carcinogenesis.